Renal Metastasis of Esophageal Squamous Cell Carcinoma- A Case Report and Literature Review - Lin, Yu-Sheng; Chiu, Kun-Yuan; Hung, Siu-Wan; Li, Hsin-Ni (Archives of Clinical and Medical Case Reports, 2018)
Esophageal cancer rarely metastasizes to the kidney. The metastatic organs known more commonly are the liver, lung, and bone. Here, we report a case of a 58 year-old male, who had been diagnosed with squamous cell carcinoma of the esophagus 22 months ago, developed renal metastasis. He subsequently received nephrectomy and adjuvant chemotherapy. We also reviewed similar cases in the literature. This case report could alert physicians caring patients of esophageal carcinoma to pay more attention to the less common renal metastasis.